MANGOKAL HOLI: BATAK CULTURAL SYMBOLISM IN THE PERSPECTIVE OF PANCASILA VALUES - Ricky Canjaya Sihombing; Marwiah Marwiah; Aloysius Hardoko; Novita Majid (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research aims to analyze the symbolic meaning and social values contained in the Mangokal Holi tradition among the Toba Batak people from the perspective of Pancasila values. A descriptive qualitative approach is used as a methodology, involving data collection through in-depth interviews with traditional leaders, community representatives, and ritual practitioners, complemented by participatory observation. The results of the study show that Mangokal Holi is not just a ritual to move the bodies of ancestors, but a blend of customary, religious, and national values, especially where the principles of divinity, humanity, and unity are reflected in intergenerational participation and social solidarity. This tradition also shows the phenomenon of cultural re-signification, observing how local customs adapt to contemporary contexts without losing their basic meaning. This research makes a significant contribution to understanding the role of local cultural practices as a medium for character education and social cohesion that is in line with the principles of Pancasila.